STUDENTS WITH BEHAVIOUR DIFFICULTIES AND LATVIAN TEACHER BELIEFS ABOUT THEM: GLOBALISATION OR GLOCALISATION IN ACTION? - Bruveris, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This paper analyses Latvian teacher beliefs about students with behaviour difficulties to ascertain whether the same issues are of concern for Latvian teachers as teachers from another system, such as Australia. Do they identify similar behaviours as of concern, do they have similar expectations and views about educating these students or are they so dissimilar that they, by borrowing from elsewhere, end up importing surrogate values and impossible solutions? This rests within a context of globalisation in education which encourages teachers to look to and borrow from foreign systems as an astute way of providing pre-tested solutions for local needs.